Anodic characteristics and stress corrosion cracking behavior of nickel rich alloys in bicarbonate and buffer solutions. (July 2016) - Zadorozne, Natalia S.; Giordano, Mabel C.; Ares, Alicia E.; Carranza, Ricardo M.; Rebak, Raul B.
Highlights: We investigate which element in alloy C-22 may be responsible for the cracking susceptibility of the high nickel alloy. Six nickel based alloys with different amount of Cr and Mo were selected for the electrochemical tests and response to SSRT. Polarization tests showed that an anodic peak appear in the passive region in Cr containing alloys. Cracking of Ni alloys in carbonate solutions seem to be a consequence of the instability of the passivating chromium oxide. Alloys containing both Cr and Mo have the highest susceptibility. Abstract: The aim of this work is to investigate which alloying element in C-22 is responsible for the cracking susceptibility of the alloy in bicarbonate and two buffer solutions (tungstate and borate). Six nickel based alloys, with different amount of chromium (Cr) and molybdenum (Mo) were tested using electrochemical methods and slow strain rate tests (SSRT) at 90 °C. All Cr containing alloys had transgranular cracking at high anodic potential; however, C-22 containing high Cr and high Mo was the most susceptible alloy to cracking. Bicarbonate was the most aggressive of three tested environments of similar pH.